THE EFFECT OFWALKING AND STEPAEROBIC EXERCISE ON PHYSICAL FITNESS PARAMETERS IN OBESE WOMEN - Akdur, Hulya; Sozen, Ahmet Bilge; Yigit, Zerrin; Balota, Nadiye; Guven, Ozen (Istanbul Univ, Faculty Medicine, Publishing Office, 2007)
Objective: The purpose of the study was to examine the effects of three different exercise regimens on physical and physiological fitness parameters in 60 sedentary obese female subjects without hypertension, diabetes, or cardiovascular disease. Materials and methods: The study groups consisted of groups whose interventions were diet and step-aerobic exercise (trice weekly, 1 hour period for 10 weeks) (n=20), diet and walking exercise (trice weekly, 1 hour walk, 10 weeks) (n=20), and diet only. The cases were followed up for changes in body weight, body mass index, body fat percentage, circumference measurements, measures of flexibility, total cholesterol and other biochemical parameters before and after the interventions. Results: Body weight, body mass index and total cholesterol changed significantly at the end of the study in step aerobic exercise and walking exercise groups. Circumference measurements and Low Density Lipoprotein (LDL) cholesterol were decreased without reaching statistical significance. Flexibility parameters increased in all groups including the controls without reaching statistical significance. Conclusion: It was concluded that step-aerobic exercise with low caloric diet seemed the most effective treatment modality.
Keywords: Obesity; step aerobic exercise